If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 10y + 3 + -3y Reorder the terms: 22 = 3 + 10y + -3y Combine like terms: 10y + -3y = 7y 22 = 3 + 7y Solving 22 = 3 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 22 + -7y = 3 + 7y + -7y Combine like terms: 7y + -7y = 0 22 + -7y = 3 + 0 22 + -7y = 3 Add '-22' to each side of the equation. 22 + -22 + -7y = 3 + -22 Combine like terms: 22 + -22 = 0 0 + -7y = 3 + -22 -7y = 3 + -22 Combine like terms: 3 + -22 = -19 -7y = -19 Divide each side by '-7'. y = 2.714285714 Simplifying y = 2.714285714
| 20x+100=180 | | 2r-7z=45 | | 12+x=90 | | 3(-14+18p)= | | 2x+10+7x=118 | | 2z+3z=30 | | -3x^2-6x=10 | | 2/5*x=12 | | 20-5c=3c+8 | | 3.6-y=-10 | | 6x/5x-25 | | x/4=25/100 | | 21=15+3(2-1) | | 30x-42=14x | | v/-80 | | 42y^8+7y^3=0 | | -2+2y=-3x | | 95.30=.55x+19.95 | | -2(x+1)=-2x+-2 | | x*(10/15)=2 | | x+43=90 | | x/10=-21 | | 25x^2+16=12 | | y=-2(7)+7 | | -5(k+6)-(2k-1)=-8k | | y=-2(6)+7 | | -6y+15=8(y-1) | | y=-2(5)+7 | | 11/4x11/3 | | 3/8*y=3 | | 42=7(-x+4) | | 4x+2.3=8 |